Sustainable Food Packaging and Consumer Purchase Intentions: A Systematic Literature Review from a Theory of Planned Behaviour Perspective - Wijesinghe, Chathura (2025)
The escalating environmental concerns related to packaging waste, resource depletion, and pollution have intensified the global push towards sustainable packaging solutions. As consumers become increasingly aware of environmental issues, their purchasing decisions are expected to shift toward eco-friendly alternatives. However, despite growing awareness, the actual adoption of sustainable packaging remains limited, often due to various psychological and practical barriers.